Strategi Counterbalance Jepang di Tengah Persaingan Kepemimpinan dengan China dalam Konteks Wacana Regionalisme Asia Timur - Pradono Budi Saputro (Universitas 17 Agustus 1945 Jakarta, 2015)
The rise of China is not only considered as an economic opportunity but also a security threat for the “East Asian” countries. China's increasing influence in the region has made the inclusive regional institutions no longer relevant because no party is able to match the economic and military power of China. Japan uses the momentum to initiate a new regionalism discourse that is more open by inviting extra-regional actors in East Asian regional institutions, as a counterbalance strategy against China.